Effect of engine failure on aerodynamic characteristics of a light transport aircraft model - Yu. S. Mikhailov (Научный вестник МГТУ ГА, 2022)
In-flight engine failure has always been a hazardous situation in case of a single-engine aircraft associated with losing altitude and making a landing within the available gliding range. In the event of a multi-engine aircraft, this situation improves markedly due to the potential flight continuation. The necessary conditions to continue a flight are available excess thrust, satisfactory aerodynamic performance, and a fixed-wing control. If the half of engine thrust is lost, which adversely affects a rate of climb, the most critical flight modes are the take-off and go-around procedures performed at low altitudes using the engine asymmetric thrust. Ensuring flight safety in these modes requires extensive experimental studies in wind tunnels to simulate the basic flight envelope with an inoperative engine.   The aim of studies is the effect of a critical engine failure on the aerodynamiccharacteristics of an aircraft model as well as ensuring the required efficiency of the flight controls to dampen the yaw and roll moments that arise during an asymmetric thrust flight.   The complexity of solving the problem is determined by the necessity of recovering from the substantial yaw, roll moments and by a significant decrease in the wing lifting efficiency along with an increase in a drag force which limits a climb rate and aircraft control. This article presents an analysis of the effect of critical engine failure on the aerodynamic characteristics of a light twin-engine transport aircraft model in the wing take-off and landing configurations. The aircraft aerodynamic configuration is made according to the classic pattern with the high-mounted tapered wing and deck-type empennage. The high lift devices comprise a double-slot hinged flap with a fixed deflector. The aircraft is equipped with a loading ramp with a relatively short flat rotatable part of the lower fuselage surface. Experimental studies of the longitudinal and lateral characteristics of the model with installed simulators of a power plant were carried out in TsAGI low-speed wind tunnel T-102. The analysis of engine failure effect on the model aerodynamics was executed in changing the load factor within the range B = 0.3…2. The capabilities to dampen the yaw and roll moments, using the primary flight controls (rudder and ailerons), were determined.